Multiple Sclerosis: Current and Future Treatment Options - Rizvi, S. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2007)
Multiple Sclerosis is an inflammatory and degenerative disorder involving the central nervous system. It primarily affects young adults and may result in significant long-term disability. The most common initial presentation is relapsing remitting, followed by a chronic progressive course. In a small number of patients the disease tends to be progressive from onset. Multiple sclerosis has traditionally been described as a demylinating disorder. There is now overwhelming evidence pointing to a very significant degenerative component. Current treatment options include immunomodulating and immunosuppressive agents as well as monoclonal antibodies and target the inflammatory component of the disease resulting in significant reduction in relapses, decrease in MRI lesion load and a modest effect on disability. There are several other biological agents being developed which target different aspects of the immunopathology of multiple sclerosis. This article will review the agents currently used in the treatment of MS and also discuss agents currently under development.
Keywords: degeneration